Effect of psychotherapy for depression on quality of life: meta-analysis. (December 2016) - Kolovos, Spyros; Kleiboer, Annet; Cuijpers, Pim
Abstract : Background: Several meta-analyses have shown that psychotherapy is effective for reducing depressive symptom severity. However, the impact on quality of life (QoL) is as yet unknown. Aims: To investigate the effectiveness of psychotherapy for depression on global QoL and on the mental health and physical health components of QoL. Method: We conducted a meta-analysis of 44 randomised clinical trials comparing psychotherapy for adults experiencing clinical depression or elevated depressive symptoms with a control group. We used subgroup analyses to explore the influence of various study characteristics on the effectiveness of treatment. Results: We detected a small to moderate effect size (Hedges' g = 0.33, 95% CI 0.24–0.42) for global QoL, a moderate effect size for the mental health component ( g = 0.42, 95% CI 0.33–0.51) and, after removing an outlier, a small but statistically significant effect size for the physical health component ( g = 0.16, 95% CI 0.05–0.27). Multivariate meta-regression analyses showed that the effect size of depressive symptoms was significantly related to the effect size of the mental health component of QoL. The effect size of depressive symptoms was not related to global QoL or the physical health component. Conclusions: Psychotherapy for depression has a positive impact on the QoL of patients with depression. Improvements in QoL are not fully explained by improvements in depressive symptom severity.